Exploring the role of the biokineticist in diabetes self-management: a survey of patients' knowledge, attitudes and perceptions about exercise. Issue 2 (4th May 2022) - Sookan, T; Vaizie, A; Pillay, T; Moodley, S; Naidoo, S; Naidoo, K
Abstract : Background : Self-management of type 2 diabetes mellitus (T2DM) in South Africa (SA) is sub-optimal, with exercise reported to be the least employed modality of self-management. This study aimed to evaluate the knowledge, attitudes and perceptions of T2DM patients regarding T2DM self-management, and to explore participants' awareness and acceptance of the role of biokineticists in the management of T2DM. Methods : This cross-sectional, descriptive study was conducted in October 2019 at an urban, district hospital in South Africa. A validated questionnaire was administered to T2DM outpatients. Participants' knowledge was evaluated by true/false questions, and their attitudes and perceptions on a five-point Likert scale. Results : Reported adherence to prescribed diabetes medication by participants ( n = 150) was high, at 96%. However, only 60% of participants reported exercising regularly; 47.3% followed a recommended diet for T2DM; and 32.7% took appropriate care of their feet. Responses given by the participants regarding their knowledge and perceptions indicated good insight into the role of exercise in the management of T2DM (94.7%). There was low awareness of the field of biokinetics, with 74% of participants admitting no knowledge of 'biokinetics'. However, after receiving information on the role of the biokineticist in T2DM, 92% of participants were willing to work with a biokineticist to manage their T2DM. Conclusion : There was low reported adherence to exercise, diet and foot care among participants, despite good knowledge about, and attitudes to, the modalities of T2DM self-management. Majority of participants (92%) expressed a willingness to work with a biokineticist to manage their T2DM. However, there is a need for greater awareness and employment of biokineticists in the multidisciplinary team to help improve the uptake of exercise by patients with T2DM.